Experimental and clinical evidence of antioxidant therapy in acute pancreatitis - EŞREFOĞLU, MUKADDES; Esrefoglu, MUKADDES (My University, 2012)
Oxidative stress has been shown to play an important role in the pathogenesis of acute pancreatitis (AP). Antioxidants, alone or in combination with conventional therapy, should improve oxidative-stress-induced organ damage and therefore accelerate the rate of recovery. In recent years, substantial amounts of data about the efficiency of antioxidants against oxidative damage have been obtained from experiments with rodents. Some of these antioxidants have been found beneficial in the treatment of AP in humans; however, at present there is insufficient clinical data to support the benefits of antioxidants, alone or in combination with conventional therapy, in the management of AP in humans. Conflicting results obtained from experimental animals and humans may represent distinct pathophysiological mechanisms mediating tissue injury in different species. Further detailed studies should be done to clarify the exact mechanisms of tissue injury in human AP. Herein I tried to review the existing experimental and clinical studies on AP in order to determine the efficiency of antioxidants. The use of antioxidant enriched nutrition is a potential direction of clinical research in AP given the lack of clues about the efficiency and safety of antioxidant usage in patients with AP
Keywords: acute pancreatitis